Case Grammar in the Movie Ã¢â‚¬Å“The GentlemenÃ¢â‚¬Â Based on the Perspective of Charles J. Fillmore - Basid, Abdul; Maghfiroh, Devi Laila (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This research aims to identify the proposition in the movie "The Gentlemen" based on Charles J. FillmoreÃ¢â‚¬â„¢s case grammar theory. This research is qualitative, descriptive, and literature research. The object of this research is the movie "The Gentlemen" directed by Guy Ritchie. The data collection techniques used are watching techniques and note-taking techniques. Data analysis through three stages: data reduction, data display, and drawing conclusions. The result of the research is that the proposition in the movie "The Gentlemen" directed by Guy Ritchie based on Charles J. Fillmore's case grammar theory consists of nine types. They are agent (A), experiencer (E), instrument (I), object (O), source (S), goal (G), location (L), time (T), and benefactive (B). Charles J. FillmoreÃ¢â‚¬â„¢s case grammar theory in the movie Ã¢â‚¬Å“The GentlemenÃ¢â‚¬Â shows that sentences always explain the correlation between verbs and nouns semantically. Thus far, proposition must always exist in a sentence because it is attached to the element of the sentence.